2013
DOI: 10.1103/physrevb.88.165416
|View full text |Cite
|
Sign up to set email alerts
|

Graphitization of single-wall nanotube bundles at extreme conditions: Collapse or coalescence route

Abstract: We determine the reaction phase diagram and the transformation mechanism of (5,5) and (10,10) single-walled carbon nanotube bundles up to 20 GPa and 4000 K. We use Monte Carlo simulations, based on the state-of-the-art reactive potential LCBOPII, that incorporates both covalent and van der Waals interactions among the tubes. At low temperature, upon increasing pressure, large (10,10) nanotubes first collapse and then coalesce, yielding almost perfect graphitic structures. In contrast, small (5,5) nanotubes do … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…8 Therefore, we may expect flattening of the horns in our CNHs samples (2-3 nm) at stresses below 0.5 GPa; this provides a stress limit beyond which additional compression would lead to the formation of graphite-like carbon. 42 Unfortunately, the stress value estimated for a similar transition in CNHs is below the detection limit in our experimental setup, and the evolution of the Raman frequencies with stress follows a linear behavior over the whole stress range monitored in this work. Moreover, the Raman spectrum of the recovered sample is presented in red in Figure 2;…”
Section: Morphological Changes Under High Stressmentioning
confidence: 64%
“…8 Therefore, we may expect flattening of the horns in our CNHs samples (2-3 nm) at stresses below 0.5 GPa; this provides a stress limit beyond which additional compression would lead to the formation of graphite-like carbon. 42 Unfortunately, the stress value estimated for a similar transition in CNHs is below the detection limit in our experimental setup, and the evolution of the Raman frequencies with stress follows a linear behavior over the whole stress range monitored in this work. Moreover, the Raman spectrum of the recovered sample is presented in red in Figure 2;…”
Section: Morphological Changes Under High Stressmentioning
confidence: 64%
“…Further, by heating SWCNTs (HiPCOs) at 1000-2400°C in a vacuum or Ar, the diameter and wall number of CNTs have been shown to increase to double-walled CNTs (DWCNTs) and even MWCNTs, while the levels of metal catalysts and carbonaceous impurities decreased [16,17]. In fact, Monte Carlo simulation have shown that heating of SWCNT bundles under high pressure (1-2 GPa) follows a graphitization pathway leading to a transformation to layered graphite crystals [18]. However, while the thermally-induced changes in the SWCNT structure and impurities have been well documented, unlike MWCNTs, there is a surprising absence of reports on the investigation in the change in physical properties, e.g.…”
Section: Introductionmentioning
confidence: 97%
“…Interestingly, under high pressure and shear, the strong deformation of the CNT can result in the delamination of flake-like graphitic structures and the formation of carbonaceous layers on the surface, providing low shear strength similar to graphite lubrication [11,27,28]. Aside from experiments, simulations have shown that in the case of high temperatures, a pressure-induced transformation of CNT towards graphite may take place [29]. Due to the promising lubrication effects, CNTs have been used as coatings or reinforcement phases in composites [8,9,11,16,22,27,28,30].…”
Section: Introductionmentioning
confidence: 99%